15th International Conference on Environmental Degradation of Materials in Nuclear Power Systems‐Water Reactors 2012
DOI: 10.1002/9781118456835.ch70
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Thermodynamical Properties of Zirconium Hydrides from First‐Principle

Abstract: Zirconium alloys are used as nuclear fuel cladding material due to their mechanical and corrosion resistant properties together with their favorable cross-section for neutron scattering. At running conditions, however, there will be an increase of hydrogen in the vicinity of the cladding surface at the water side of the fuel. The hydrogen will diffuse into the cladding material and at certain conditions, such as lower temperatures and external load, hydrides will precipitate out in the material and cause well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Both diagrams agree well in establishing the phase fields of the δ-and ε-hydrides with homogeneity ranges on the basis of the stoichiometric compounds ZrH 1.5 (experimentally established value is ZrH 1.66 , [35] . Partial molar entropy of hydrogen: comparison of the results of modeling (left) and experimental data [16]; black solid line -the results of thermodynamic assessment in [55] and experimental work [54] Figure 11.…”
Section: Figuressupporting
confidence: 52%
See 3 more Smart Citations
“…Both diagrams agree well in establishing the phase fields of the δ-and ε-hydrides with homogeneity ranges on the basis of the stoichiometric compounds ZrH 1.5 (experimentally established value is ZrH 1.66 , [35] . Partial molar entropy of hydrogen: comparison of the results of modeling (left) and experimental data [16]; black solid line -the results of thermodynamic assessment in [55] and experimental work [54] Figure 11.…”
Section: Figuressupporting
confidence: 52%
“…Calculation using ThermoCalc; (b) experimental phase diagram [48]. Both diagrams agree well in establishing the phase fields of the δ-and ε-hydrides with homogeneity ranges on the basis of the stoichiometric compounds ZrH 1.5 (experimentally established value is ZrH 1.66 , [35]). …”
Section: 21mentioning
confidence: 84%
See 2 more Smart Citations
“…Some works have focused on the octahedral site as the main location for H atom solution, however such works appear to be in the minority 23,24 . It has been theoretically predicted that the FCT structure of ZrH 2 can have another stable phase for c/a ¿ 1 25,36 . Zhu et al 16 studied the ordered hydride phases using DFT; they concluded that δ-ZrH 1.5 is thermodynamically less stable than the other phases at high temperature.…”
Section: Introductionmentioning
confidence: 99%